2015
DOI: 10.7763/ijssh.2015.v5.518
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Influence on Muslim Flood Victim Wellbeing in Flood Prone Districts in Malaysia

Abstract: Index Terms-Demographic characteristic, education level, Islamic teaching knowledge, young adult respondents, flood disaster coping mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Looking from an Islamic perspective, this study looks at spirituality as one of religion's dimensions. Many researchers (e.g., Krauss, Hamzah, Juhari, & Abd Hamid, 2005;Radzi, Sipon, Othman, Nik Nazali, & Abd Ghani, 2015) confirm that Islam implies the sanctification of all daily living into worshipful acts that unify life, consistent with "tawhidic" principles of the divine unity. Bhui, King, Dein, and O'Connor (2008) found that spiritual coping practices were indistinguishable from religious coping among Muslims.…”
mentioning
confidence: 89%
“…Looking from an Islamic perspective, this study looks at spirituality as one of religion's dimensions. Many researchers (e.g., Krauss, Hamzah, Juhari, & Abd Hamid, 2005;Radzi, Sipon, Othman, Nik Nazali, & Abd Ghani, 2015) confirm that Islam implies the sanctification of all daily living into worshipful acts that unify life, consistent with "tawhidic" principles of the divine unity. Bhui, King, Dein, and O'Connor (2008) found that spiritual coping practices were indistinguishable from religious coping among Muslims.…”
mentioning
confidence: 89%